2017
DOI: 10.1016/j.jneumeth.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A novel operant task to assess social reward and motivation in rodents

Abstract: This task allows for detailed and direct assessment of social and non-social rewards that may serve as effective behavioral reinforcers in this operant conditioning model, and it can be used to investigate the neural mechanisms regulating motivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…Rather than allowing mice to passively experience a social stimulus, such paradigms require effort from subjects to obtain a social reward, potentially rendering it more salient. Similar studies in hamsters have found that subjects work equally hard for social rewards as food rewards [37]. Social feedback appears to be intrinsically rewarding across social species, causing increases in dopamine that mediate appetitive learning via behavioral reinforcement [38].…”
Section: Figure 4 Correlation Between Arousal Behaviors During Playbmentioning
confidence: 82%
“…Rather than allowing mice to passively experience a social stimulus, such paradigms require effort from subjects to obtain a social reward, potentially rendering it more salient. Similar studies in hamsters have found that subjects work equally hard for social rewards as food rewards [37]. Social feedback appears to be intrinsically rewarding across social species, causing increases in dopamine that mediate appetitive learning via behavioral reinforcement [38].…”
Section: Figure 4 Correlation Between Arousal Behaviors During Playbmentioning
confidence: 82%
“…Moreover, as bees remain sensitive to social stimuli into adulthood, exposure to the hive and presumed interactions with other bees would enable this conditioned learning. Vertebrates value social stimuli as rewarding (Borland et al, 2017) and can associate social cues with a location (Calcagnetti and Schechter, 1992). Furthermore, vertebrates respond to social cues as they do to food rewards (Mühlhoff et al, 2011) and the same mesocorticolimbic system is involved (Dölen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in social reward As mentioned above, the rewarding nature of social interactions has recently been compared explicitly between males and females, using Syrian hamsters as an animal model. While not a great deal is known about the social behavior of hamsters in the field, laboratory studies show social interactions to be highly rewarding in this species [8,115,116]. Hamsters have robust skills in social recognition of, and communication with, conspecifics [117,118].…”
Section: Sex Differences In Mesolimbic Dopamine Signalingmentioning
confidence: 99%